Copper Winding Voice Coil Speaker Microcontroller Based - Adi Kurniawan Saputro; Hanifudin Sukri; Andre Putra Pratama; Koko Joni; Achmad Fiqhi Ibadillah; Monika Faswia Fahmi (JEECS (Journal of Electrical Engineering and Computer Sciences), 2024)
The voice coil is a vital speaker component, producing sound through electromagnetic vibrations. Generally, commercially available voice coils do not meet standard quality specifications, especially in terms of copper quality and adhesive strength. This problem often leads to issues such as coil burning or breakage during operation. On the other hand, ordering custom voice coils through manual winding processes requires considerable time. This study aims to address these limitations by designing an automated coil winding device that employs Pulse Width Modulation (PWM) techniques to control the speed of a DC motor, enabling the production of voice coils with specifications and durability tailored to specific needs. An Arduino Nano microcontroller controls the system and consists of a BTS 7960 motor driver, a Direct Current (DC) motor, an optocoupler sensor, a rotary encoder, a 4x4 keypad, and an LCD display with an I2C interface. Coil durability testing was conducted using an ohmmeter and an amplifier with a transformer ranging from 20A 45V to 30A 45V. The testing results indicate that coils produced with the automated winder can be adjusted to approach the 8-ohm specification, with a tolerance of 0.1 to 0.3 ohms, suitable for speaker requirements. The comparison results show that commercial voice coils exhibit resistances below 8 ohms, with the lowest resistance measured at 4.9 ohms for larger coils. During power testing, coils with a diameter of 35.5 mm and copper wire diameters of 0.20 mm and 0.23 mm broke when tested with a 20A 45V amplifier. In contrast, commercial coils remained stable up to an input power of 372 W and output power of 273 W, although a burning odor was detected. These findings indicate that the copper quality in commercial coils is superior in resisting amplifier power up to 30A 45V compared to coils produced with the automated device.